Prediction of adenomyosis according to revised definitions of morphological uterus sonographic assessment features - Yavuz, Onur; Akdöner, Asli; Özgozen, Mehmet Eyüphan; Ertan, Begüm; Kurt, Sefa; Ulukuş, Emine Cagnur; Güney, Mehmet (Frontiers in Medicine, 2024)
Objectives: To predict the diagnosis of adenomyosis by revised definitions of morphological uterus sonographic assessment (MUSA) features in individuals who had hysterectomy. Methods: This was a retrospectivexcohort research conducted at a tertiary facility. Between January 2022 and January 2023, 196 individuals who had hysterectomy were analyzed in the research. The revised definitions of MUSA features of adenomyosis approach was used to record the direct and indirect results of the sonography. The cases were classified as Group 1 (Adenomyosis; n=40, 20.4%) and Group 2 (Control; n=156, 79.6%) according to histopathologyxreports. Results: Hyperechogenic islands and echogenic subendometrial buds and lines were the most predictive direct features (p=0.02). Globularxuterus and irregular junctionalxzone were the most predictive indirect features (p=0.04; p=0.03, respectively). Among all and indirect features, globularxuterus was the most predictive (p=0.02). Total feature >4 was determined as the significant cut-off value to predictxadenomyosis (p<0.001).This study shows that combinations with a total number of features >4 can be practically used in the evaluation of adenomyosis using the revised definitions of MUSA features.